ANSWER
![y=-2(x+1)^2-4](https://img.qammunity.org/2023/formulas/mathematics/college/i3ikdlyzfu6ncq4m2n2ewavlmjx1ofhhcn.png)
Step-by-step explanation
The vertex form of a quadratic equation is:
![y=a(x-h)^2+k](https://img.qammunity.org/2023/formulas/mathematics/college/97p0xsjs0cwme4ddvwkim2cbbqprhnlhsv.png)
where (h, k) = vertex
Let us substitute the given vertex and the given point into the equation to find the value of the constant a.
That is:
![\begin{gathered} -36=a(-5-(-1))^2+(-4) \\ -36=a(-5+1)^2-4 \\ -36=a(-4)^2-4 \\ -36=16a-4 \\ 16a=-36+4=-32 \\ \Rightarrow a=(-32)/(16) \\ a=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ppzgexnx2z18ixxegpxrbeju39b9sw194s.png)
That is the value of the constant a. Now we can write the quadratic function using the constant a and the vertex:
![\begin{gathered} y=-2(x-(-1))^2+(-4) \\ y=-2(x+1)^2-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k8j6ktp0ng24hzq2faztc4lhnqk8n27aih.png)
That is the function.